1999
DOI: 10.1007/s002130050852
|View full text |Cite
|
Sign up to set email alerts
|

Acute fluoxetine treatment potentiates amphetamine hyperactivity and amphetamine-induced nucleus accumbens dopamine release: possible pharmacokinetic interaction

Abstract: Amphetamine stimulates locomotor activity, in large part by activating central dopaminergic systems. Serotonin shares on overlapping distribution with dopamine and has been shown to modulate dopaminergic function and dopamine-mediated behaviors. The present study examined whether increasing serotonergic function, via the selective serotonin reuptake inhibitor fluoxetine, would alter the stimulatory effects of amphetamine on locomotor activity and dopamine overflow in the nucleus accumbens. In addition, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 41 publications
3
13
1
Order By: Relevance
“…If acute administration of fluvoxamine impedes the metabolism of mazindol via inhibition of metabolic enzymes, increased brain concentrations of mazindol could contribute to the observed hyperactivity. A similar mechanism was proposed for the facilitation of amphetamine-induced hyperactivity and DA efflux in NAc by systemic fluoxetine; in that study, increased amphetamine levels were observed in the NAc of fluoxetine-treated rats (Sills et al 1999a). Fluvoxamine has been shown to inhibit cytochrome P450 isozymes that catalyze the oxidative metabolism of certain drugs and could, therefore, increase brain levels of drugs metabolized by these isozymes (Hiemke and Hartter 2000).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…If acute administration of fluvoxamine impedes the metabolism of mazindol via inhibition of metabolic enzymes, increased brain concentrations of mazindol could contribute to the observed hyperactivity. A similar mechanism was proposed for the facilitation of amphetamine-induced hyperactivity and DA efflux in NAc by systemic fluoxetine; in that study, increased amphetamine levels were observed in the NAc of fluoxetine-treated rats (Sills et al 1999a). Fluvoxamine has been shown to inhibit cytochrome P450 isozymes that catalyze the oxidative metabolism of certain drugs and could, therefore, increase brain levels of drugs metabolized by these isozymes (Hiemke and Hartter 2000).…”
Section: Discussionsupporting
confidence: 70%
“…The ability of cytochrome P450 isozymes to contribute to the transformation of mazindol into imidazole-3-one, its primary metabolite in the rat, is currently unknown (Dugger et al 1979). In vivo microdialysis is one strategy that could be used to determine the extent to which the observed synergism between fluoxetine and mazindol might be related to fluvoxamineevoked increases in brain concentrations of mazindol (Sills et al 1999a). However, we have recently shown that microinjections of fluvoxamine into the shell of the NAc result in an immediate enhancement of hyperactivity evoked by systemic cocaine (McMahon et al 2000), a finding difficult to reconcile with a mechanism dependent upon inhibition of metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute fluoxetine or citalopram increases amphetamine-induced hyperlocomotion Millan et al, 2003) but has no effect on phencyclidine-induced model (Redmond et al, 1999). Repeated fluoxetine or citalopram treatment tends to enhance amphetamine-induced hyperlocomotion (Arnt et al, 1984;Sills et al, 1999Sills et al, , 2000 and phencyclidine-induced hyperlocomotion (Redmond et al, 1999). Taken together, a combination of repeated amphetamine and phencyclidine hyperlocomotion models may be utilized to distinguish anxiolytics and antidepressants from antipsychotics.…”
Section: Acknowledgementsmentioning
confidence: 99%